Suwanee Lumber Company (B) - Elias, Jaan; Blumenthal, Adam; Shovlin, James; Tookes, Heather E. (London : Yale School of Management, 2020)
In early 2018, Blue Wolf Capital Management received an offer to sell both its mill in Arkansas (Caddo) and its mill in Florida (Suwanee) to Conifex, an upstart Canadian lumber company. Blue Wolf hadn't planned to put both mills up for sale yet, but was the deal too good to pass up?
Orginally Published InElias, J., Blumenthal, A., Shovlin, J., & Tookes, H.E. (2020). Suwanee Lumber Company (B). 20-011. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sale of business enterprises -- Case studies; Venture capital -- Case studies